2011
DOI: 10.2298/bah1103975o
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cows welfare quality in loose vs tie housing system

Abstract: The subject of this research was to determine the effect of the housing system on quality of welfare of dairy cattle in Serbia. Study was realized on six farms, capacity of 30 to 900 cows, with loose and tie housing system. Assessment of the welfare quality parameters was done by using the Welfare Quality ® Assessment Protocol for Cattle, 2009. Results of the research show that the welfare quality of dairy animals is under the significant effect of housing system, and that loose system has the advantage when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 13 publications
6
31
2
Order By: Relevance
“…The higher dystocia rate in THS than in LHS is probably caused by the lack of exercise (Gustaffson, 1993;Mee, 2004). Mortality was significantly higher in THS than in LHS (P<0.05), similar to that recorded by Ostojic-Andric et al (2011) in a recent study in Serbia. Thomsen et al (2006) found that tie stalls tended to have higher mortality rates than free stalls with cubicles, although the difference was not statistically significant.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…The higher dystocia rate in THS than in LHS is probably caused by the lack of exercise (Gustaffson, 1993;Mee, 2004). Mortality was significantly higher in THS than in LHS (P<0.05), similar to that recorded by Ostojic-Andric et al (2011) in a recent study in Serbia. Thomsen et al (2006) found that tie stalls tended to have higher mortality rates than free stalls with cubicles, although the difference was not statistically significant.…”
Section: Resultssupporting
confidence: 60%
“…The farms with LHS were in the enhanced (21 farms) and "acceptable" (9 farms) categories, while those with THS were categorised as enhanced (5 farms), acceptable (19 farms) and not classified (6 farms) ( Figure 1). No farm had an excellent level, similar to the results obtained in other countries (De Vries et al, 2011;Keeling, 2009;Ostojic-Andric et al, 2011). Studies about cattle welfare assessment using the WQ protocol in different housing systems are not widely published, making it difficult to compare the final results.…”
Section: The Final Assessmentsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the zootechnical constructions most suitable to the production system demand increasingly different solutions and adaptations needs (LOPES et al, 2012). Productive efficiency in free-stall confinement is highly affected by poor design of the confinement projects, which usually limits interventions in the environment thermal control and disfavor the routine chores in the operation, maintenance, hygiene and animals handling (PERISSINOTTO et al, 2009;OSTOJIĆ-ANDRIĆ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%